2021
DOI: 10.1108/jrme-05-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of strategy on entrepreneurial orientation and performance

Abstract: Purpose This study aims to examine the effect of entrepreneurial orientation (EO) on performance and mediation differentiation strategies and market development in small and medium enterprises (SMEs). Design/methodology/approach This research was conducted using a survey method with a population of furniture SMEs in Jepara, Central Java, Indonesia using a sample area by collecting 158 questionnaires. The data analysis method used the partial least square. Findings The result shows that EO has an impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 118 publications
0
13
0
Order By: Relevance
“…It is important to understand the nature of SMEs and particularly those that have resource limitations, which undeniably makes it difficult to achieve competitive advantage. In this context, the approaches that are undertaken in EM being adopted by SMEs that JRME 25,3 incorporate strategic orientation dimensions include market, customer, entrepreneurial and innovation orientation (Budiati et al, 2021;Jones and Rowley, 2009). These strategic orientations assist SMEs to develop superior performance and competitive advantage despite one's resource scarcity (Chahal et al, 2016).…”
Section: Merging Marketing Into Entrepreneurial Contextmentioning
confidence: 99%
“…It is important to understand the nature of SMEs and particularly those that have resource limitations, which undeniably makes it difficult to achieve competitive advantage. In this context, the approaches that are undertaken in EM being adopted by SMEs that JRME 25,3 incorporate strategic orientation dimensions include market, customer, entrepreneurial and innovation orientation (Budiati et al, 2021;Jones and Rowley, 2009). These strategic orientations assist SMEs to develop superior performance and competitive advantage despite one's resource scarcity (Chahal et al, 2016).…”
Section: Merging Marketing Into Entrepreneurial Contextmentioning
confidence: 99%
“…Besides, there are no similar studies undertaken in daycare centers. Nevertheless, significant results were found in numerous studies focusing on the link that occurs between entrepreneurial orientation and entrepreneurial strategy in the company (Budiati et al, 2021;Kantur, 2016;Mustafa et al, 2021;Shah & Ahmad, 2019). Hence, it is necessarily and urgently important to conduct the study on the relationship between entrepreneurial orientation and entrepreneurial strategy in foster centers in Indonesia.…”
Section: Problem Statementsmentioning
confidence: 99%
“…The study conducted by Ziyae & Sadeghi (2021) involving 103 financial companies in Iran denoted a significant mediation effect that occured between business performance and entrepreneurial orientation. Besides, Budiati et al (2021) asserted that there was an effect found in the strategy mediation, affecting business performance and entrepreneurial orientation in 158 SMEs in Indonesia. Conversely, in the relationship that occurs between business performance and entrepreneurial orientation of 133 IT and telecommunication companies in Pakistan, it was found that the mediation effect of the entrepreneurial strategy was considered insignificant (Mustafa et al, 2021).…”
Section: Entrepreneurial Strategy Mediates Entrepreneurial Orientatio...mentioning
confidence: 99%
“…Husairi et al [ 23 ] point out that new insights must be infused into market entry strategies to mitigate late market entry effects, particularly for late entrants characterized by low resource availability. The market entry literature has struggled to propose marketing strategies from a resource-constrained firm's lens; therefore, an entrepreneurial marketing approach seems to fit this need [ 24 ]. Further, the extant literature does not illuminate the utility of EM-oriented MPS and culturally-driven customer CRM to investigate the indirect effects of time in the market and market share.…”
Section: Introductionmentioning
confidence: 99%